Novel rare earth (RE-La, Er, Sm) metal doped ZnO photocatalysts for degradation of Congo-Red dye: Synthesis, characterization and kinetic studies. (1st June 2019) - Pascariu, Petronela; Cojocaru, Corneliu; Olaru, Niculae; Samoila, Petrisor; Airinei, Anton; Ignat, Maria; Sacarescu, Liviu; Timpu, Daniel
Abstract: Synthesis and characterization of novel ZnO:RE nanostructured materials doped with 1% rare-earth elements (RE = La, Er, Sm) and their testing for photocatalytic applications were reported. The materials were obtained via electrospining, followed by calcination at 700  ° C. The samples were characterized in terms of surface morphology (SEM, TEM), crystalline structure (XRD) and band gap energies. TEM results showed the formation of a unidimensional structure (ZnO) with an average fiber diameter of 600 nm and a morphology consisting of interconnected nanoparticles having dimensions in the range 25–134 nm (ZnO doped with RE). Optical properties were explored by using UV-VIS reflectance spectra and the band gap values were determined with the Kubelka–Munk function (KM) by plotting [ F(R ∞ )hν ] 2 vs. hʋ . The photocatalytic activity was assessed by studying the degradation of a water-soluble anionic dye (Congo-Red) under UV-light irradiation. The data related to photodegradation kinetics were reasonably fitted to the pseudo-first-order kinetic model. Results revealed that the values of the rate constants ranged from 10 −3 to 10 −2 min −1, depending on the material type and initial dye concentration. In addition, Langmuir-Hinshelwood (LH) model was utilized to explain the kinetics of photodegradation reactions of CR in the presence of (ZnO:Sm) sample. The LH approach suggested that both adsorption and photocatalysis phenomena prevailed in the process of dye removal. Optimal conditions of experiments were determined empirically by employing the gradient method. Thus, a maximal value of color removal efficiency (95.8%) was observed experimentally for the initial dye concentration of 10.7 mg/L and 0.236 g/L catalyst dosage (ZnO:Sm). Furthermore, a successful recovery of the spent catalyst was accomplished by thermal activation. Graphical abstract: Image 1 Highlights: ZnO:RE (RE = Sm, Er, La) materials were produced by elctrospinning-calcination method. ZnO:RE showed improved photocatalytic activity with about 23% comparing to ZnO. The highest photocatalytic efficiency (95.8%) was observed for ZnO:Sm. Kinetics of photodegradation reactions were detailed. The photodegradation of CR dye was possible at low catalyst dosage (0.236 g/L).